PUBLIC-PRIVATE PARTNERSHIP - ONE OF THE WAYS TO ENHANCE THE EFFECTIVENESS OF AIR NAVIGATION SERVICES - R. G. Malyshev (Научный вестник МГТУ ГА)
The article examines existing in different countries legal forms providers for Air Navigation Services. The tendency of transition from state organizations to different form public-private partnership, until fully private enterprises. Based on the positive experience of the world is invited to reform the air navigation system of air traffic services of Russian on a public-private partnership.